Responsible mining and sustainability in Nigeria: the case of Bitumen - Akinyosoye, Oluwole Olafusi (My University, 2020)
The last few decades have been marked by a sense of urgency regarding the sustainable use of the earth’s natural resources. During this period, the mining and minerals industries have received particular attention in relation to their perceived destructive impact on the environment. Within this context, the discourse of responsible mining has relatively recently emerged as a possible route towards more sustainable mineral exploitation that could be the basis for sustainable development in the future. For some commentators the idea of responsible mining is an oxymoron: mineral exploitation is always environmentally too costly. For other commentators, effective management of mineral resources provides a realistic path to sustainable development for resource rich but economically poor nations. One of the key components of responsible mining is "good governance": i.e. the presence of a broadly legitimate and democratic form of governing society, which includes a balance of power in the administration of a country between the effective institutions of state and civil society. However, the past decades have suggested that there is an inherent crisis of poor governance in many developing countries, which has been identified as one of the drivers of change to initiate sustainable development. This research report offers an exploration of these two intersecting concepts of responsible mining and governance in Nigeria, in the context of the proposed economic diversification strategy through non-oil and solid minerals development. The study focusses on what might be termed the paradox of sustainable futures in Nigeria: with the proposed exploitation of bitumen reserves in a country that has a poor social and environmental reputation for oil mining. What are the prospects that bitumen could provide resources for sustainable growth in Nigeria? Despite relatively high rates of growth in the Nigerian economy in the past few years, the Nigerian economy has traditionally been overly dependent on oil and gas extraction, and the gradual decline over the past two decades has seen an overall decline in development in the country. As a result, the government has identified other resource potentials, in this context, to exploit the vast bitumen reserves in Nigeria. Whilst the idea to mine bitumen spawns the rhetoric of development in the area and huge revenues to the government for national development purposes, there is a need to explore the paradox of development from this form of mining. More importantly is the impending impact on the indigenous people, which is influenced by certain factors, especially the network of governance, to address the challenges of minerals development in Nigeria. In this context, this study is an attempt to explore the possibilities of and anxieties regarding sustainable futures in the context of the impending bitumen exploitation. The study involved 3 months of field research in Agbabu in Ondo State, Nigeria, one of the areas that will be most affected by the proposed bitumen mining. The area is largely rural, with traditional forms of land ownership and farming practices that are integral to the economic opportunities within the community. Thus, to obtain detailed knowledge of the dynamics of exploiting bitumen, this study applied a qualitative research design to conduct a case-study research on Agbabu in Ondo state, Nigeria. The review of relevant literature, focus group discussion, in-depth interviews, and key informant interviews were relevant tools that provided the data for the study. With these tools, the study gathered data from a range of respondents which included the local population, government officials and professionals who hold esteemed positions in this study concerning their experiences and opinions’ on the proposed bitumen project. The study found that despite the welcome idea of bitumen development, local mining communities still struggle with issues of being marginalised and excluded from decision-making processes in matters related to their indigenous space.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Geography, Archaeology, and Environmental Studies, University of the Witwatersrand, Johannesburg, 2020.
Keywords: Bitumen exploitation; Responsible mining; Sustainable development; Governance; Local communities; economic growth; Development; SDG-7: Affordable and clean energy; SDG-12: Responsible consumption and production